Analisis Teknik Lompat Jauh Gaya Jongkok Pada Siswa SMP Negeri 7 Bengkulu Selatan - Syarveno, Ericx (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the level of long jump skills in squat style students at SMP Negeri 7 South Bengkulu. This research is quantitative research using survey analysis techniques. The population in this research is 32 students of SMP Negeri 7 South Bengkulu. To obtain samples in this research, total sampling techniques were carried out. The research results showed that the majority of students at SMP Negeri 7 South Bengkulu showed a sufficient level of competence in the sport of long jump. This can be seen from the average score obtained on the long jump skills test, where the majority of students were able to demonstrate good basic technique and sufficient distance to be considered competent in this sport. concluded that in the Quite Competent category with a class average of 8.78 in the results of the long jump skills test of 32 students at SMP Negeri 7 South Bengkulu